The World of Still Life is a World that is Motionless or that Has Become Motionless. - Mukhiba Boltaevna Sulaimonova (Research Parks Publishers, 2021)
The world of still life is a world that is motionless or that has become motionless. If the composition includes an image of a living, capable of movement: a fly crawling over fruit, a butterfly fluttering over flowers, or, finally, a person offering it to the audience, then all this living in a still life serves only to reveal the specifics of dead nature.